ANALISIS KESTABILAN LERENG BERDASARKAN METODE ROCK MASS RATING PADA PT. INDOCEMENT TUNGGAL PRAKARSA Tbk, KABUPATEN BOGOR, PROVINSI JAWA BARAT: ANALYSIS OF SLOPE STABILITY BASED ON THE ROCK MASS RATING METHOD AT PT. INDOCEMENT TUNGGAL PRAKARSA Tbk, BOGOR DISTRICT, WEST JAVA PROVINCE - Hadi Taqiuddin, Akrom; Ronoatmojo, Imam Setiaji (Universitas Trisakti, 2024)
Weathering and the geological structure of the area affect slope stability. PT. Indocement Tunggal Prakarsa Tbk, Citeureup District, Bogor Regency, West Java Province, is the subject of this research. By calculating the safety factor value based on the Rock Mass Rating (RMR) using the Spencer method using Rocscience Slide 6.0 software, researchers hope to ensure slope stability. In fact, based on the slope stability analysis, it has a safety factor value of 0.900, so it is not in accordance with the Minister of Energy and Mineral Resources regulation 1827/K/30/MEM/2018. Based on this, recommendations for slope analysis of the research area have been made with a safety factor value of 1.232 in accordance with applicable regulations.